Superoxide Dismutase Participation in Sperm Capacitation - Payan-Carreira, Rita; Santos, Dario (My University, 2022)
Maturation of the spermatozoa in the female genital tract involves two crucial reactions that confer the sperm the ability to interact and fuse with the oocyte: capacitation and acrosome reaction. It is now commonly believed that sperm capacitation and the acquisition of progressive motility is a redox-mediated process. Oxidative stress relies on a balanced mechanism between the production of reactive species and the activity of scavenger molecules. Superoxide Dismutase (SOD) is one of the antioxidant enzymes whose presence was confirmed in the semen of several mammalian species. Also, SOD content is associated with the ability to resist freezing in bull´s semen. SOD presence in the ejaculate was confirmed in the man, bull, boar, stallion, and dog, even though the amount of the enzyme varies significantly between species. When separated from the seminal fluid, such as during sperm transport in the genital tract or dilution for artificial insemination, the limited SOD sperm content, along with its limited transcriptional ability, fragilizes sperm defenses. Oxidative stress has often been associated with precocious capacitation following freezing/thawing procedures. The differences in the antioxidant mechanism were hypothesized as the reason for the different species´ cryotolerance and the existing good and bad freezers within the same species. This possibility led to the supplementation of cryopreservation media with antioxidant enzymes, including SOD. Recently published papers suggested that cryopreservation may subject this enzyme to redox modifications of the molecule, contributing to a redox increase. Nonetheless, the role of SOD in the capacitation process is not consensual. It has been proposed that, in human and bovine, SOD suppress capacitation through the inhibition of the peroxynitrite pathway. SOD activity has been correlated in vitro with the percentage of motile sperm in humans and pigs, either in fresh or freeze/thawed samples. It has been proposed that the thermal and oxidative stress associated with sperm technologies may decrease/deplete the endogenous SOD activity and therefore withdrawn SOD inhibitory effect over capacitation. In the stallion, SOD addition was unable to prevent induced capacitation and acrosome exocytosis. This chapter intends to discuss the role of SOD in sperm capacitation.
Keywords: oxidative stress; enzymatic antioxidants; fertilizing ability; capacitation; acrosome reaction; resistance to cryopreservation; sperm